نماذج من الأساليب النبوية وعلاقتها بالأساليب التدريسية المعاصرة - Ibtissem Ghanem (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2019)
The current research paper aims to identify the Prophet’s Mouhamed (PBHU) characteristics and styles and its relation into contemporary teaching methods by mentioning examples from his Prophetic Tradition (Sunnah) .The study was limited to the Prophet's Mouhamed methods in the field of education as: problem solving, conceptual maps and brainstorming. One of the findings said that the Prophet Mouhamed (PBUH) drew the basic principles of contemporary teaching methods, and his Prophetic Tradition is rich with  different teaching methods which consequently should be used for identifying  and applying other methods in the field of education.